2010
DOI: 10.1051/epjpv/2010001
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-thin crystalline silicon films produced by plasma assisted epitaxial growth on silicon wafers and their transfer to foreign substrates

Abstract: We have developed a new process to produce ultra-thin crystalline silicon films with thicknesses in the range of 0.1−1 μm on flexible substrates. A crystalline silicon wafer was cleaned by SiF4 plasma exposure and without breaking vacuum, an epitaxial film was grown from SiF4, H2 and Ar gas mixtures at low substrate temperature (T sub ≈ 200• C) in a standard RF PECVD reactor. We found that H2 dilution is a key parameter for the growth of high quality epitaxial films and modification of the structural compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
(21 reference statements)
0
17
0
1
Order By: Relevance
“…1) shows that the film is 100% c-Si. As previously shown [12,17], epitaxial films can be described by a three layer model: i) a very thin (~1 nm) interface layer between the substrate and the film made up of a mixture of c-Si and voids, ii) a bulk layer modeled by a mixture of monosilicon [18], large and small grain polysilicon [19], and iii) a roughness layer made up of a mixture of c-Si and voids. The very thin interface layer is responsible for the interference fringes observed in the low photon energy range (< 3 eV).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1) shows that the film is 100% c-Si. As previously shown [12,17], epitaxial films can be described by a three layer model: i) a very thin (~1 nm) interface layer between the substrate and the film made up of a mixture of c-Si and voids, ii) a bulk layer modeled by a mixture of monosilicon [18], large and small grain polysilicon [19], and iii) a roughness layer made up of a mixture of c-Si and voids. The very thin interface layer is responsible for the interference fringes observed in the low photon energy range (< 3 eV).…”
Section: Resultsmentioning
confidence: 94%
“…While much more work is required to better understand the growth process, there is no doubt that the possibility of growing crystalline silicon films in the same equipment as that used for silicon thin films opens new perspectives. A recent example is the production of thin crystalline foils on foreign substrates [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pursuing this approach, we have studied the growth of thick epitaxial layers and have found that the epitaxial growth can be sustained up to a thickness of 3 µm at such low-temperature conditions. Moreover, by using an SiF 4 plasma etching step on the wafer substrate before deposition, we have found that it is possible to produce a crystalline silicon layer having a porous interface with the crystalline silicon wafer, which allows to easily detach the epitaxial film from the substrate [8,9]. In this way it is possible to produce thin and flexible crystalline silicon wafers that could be used for electronic devices, in a similar way to the "smart-cut" process [10].…”
Section: Introductionmentioning
confidence: 99%
“…For further cost reduction of monocrystalline Si solar cells (SCs), both decreasing material usage by means of thin film and increasing power generation by increasing energy conversion efficiency are two effective methods. As for the approach by means of thin films, transferring of thin epitaxially grown Si film on Si wafer to foreign substrates is a promising method [1][2][3]. As for the latter approach, several structures of Si SC have been proposed and realized.…”
Section: Introductionmentioning
confidence: 99%